Constitutional Justice - MOROȘTEȘ, Anca Florina; STOICU, Narcisa Mihaela (Journal of Legal Studies, 2017)
The paper with the title "Constitutional Justice" aims to analyse a topic of urgent actuality and of particular importance in the contemporary society. We have tried to show in this paper the importance of the Constitutional control in the rule of law. Starting from the idea of necessity of existence of a Constitution in a democratic State and, implicitly, of a body to follow-up the compliance with its provision, we have tried to highlight in this paper the role of Romanian Constitutional Court and not only, by presenting one of its most important attributions which is the control of the law constitutionality